A molecular docking study of Rhizoma Atractylodis and Rhizoma Atractylodis Macrocephalae herbal pair with respect to type 2 diabetes mellitus - Che Chen; Sheng Zhou; Qinggang Meng (Journal of Traditional Chinese Medical Sciences, 2018)
Objective: To investigate the action mechanism of Rhizoma Atractylodis (Atractylodes lancea (Thunb.) Dc.) and Rhizoma Atractylodis Macrocephalae (Atractylodes macrocephala Koidz.), a two-herb ancient traditional Chinese medicine used to treat type 2 diabetes mellitus, using molecular docking. Methods: The Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform was searched for compounds in the two herbs and oral bioavailability and drug-likeness values were used to select compounds. The target proteins were selected based on a survey of the literature and related databases, and three receptors closely related to type 2 diabetes were chosen: insulin receptor, peroxisome proliferator activated receptor and dipeptidyl peptidase-IV. Molecular docking was performed using the CDocker module in Discovery Studio software. The interactions between targets and ligands were observed and analyzed, including the mode of action. Results: Nineteen compounds from the herbal pair interacted with the insulin receptor, the peroxisome proliferator activated receptor and dipeptidyl peptidase-IV. Among them, 10 compounds bound successfully with all three targets, one compound bound with two targets, and eight compounds bound with one target. According to CDocker Interaction Energy, most compounds from the herbal pair had good binding activities with receptors and nine compounds had even higher scores than those of the original ligands. These data indicate that these compounds may be active in reducing blood glucose levels for the treatment of type 2 diabetes. Conclusion: Multiple compounds in the Rhizoma Atractylodis-Rhizoma Atractylodis Macrocephalae herbal pair can affect multiple human targets related to type 2 diabetes. Keywords: Herbal pair, Pharmacological mechanism, Molecular docking, Type 2 diabetes mellitus